In the Presence of Biomedicine: Ayurveda, Medical Integration and Health Seeking in Mysore, South India - Tapio Nisula (Anthropology & Medicine Vol. 13, No. 3, December 2006, pp. 207-224, 2006)
This paper is based on a research on medical integration and health seeking in Mysore, South India. It explores the use of Ayurvedic services, the impact of biomedicine on Ayurvedic practices and the meaning of instruments with respect to the expectations of patients and healers. The research was done during 2002 and 2003. The empirical data are derived from interviews, participant observation and survey material. Participant observation was carried out in two hospitals and nine clinics offering Ayurvedic services; 25 Ayurvedic practitioners and 30 patients were interviewed. A total of 233 respondents were surveyed in the University of Mysore and on trains and buses between Mysore and Bangalore. Results suggest that Ayurvedic medicine serves as a health reserve in urban Mysore. For the majority of informants biomedical treatment was an obvious choice of treatment, a form of therapy that was taken for granted, if compared with the preference for Ayurvedic services, which were usually utilized because of the failure of biomedicine. Regarding the position of Ayurveda, three issues are vital: first, the lack of experience and first-hand knowledge of Ayurveda on the part of health seekers, secondly, the significance of instruments, tools and technology as regards the expectations of proper consultation, and thirdly, the impact of medical integration, which seems to be critical for modern Ayurveda to thrive in the health market. In short, in order to gain popularity in an urban context, Ayurvedic practitioners favour institutional integration and adoption of items and practices particular to biomedicine.